Capturing women's voices: lived experiences of incivility during childbirth in the United States. Issue 7 (9th August 2021) - Vargas, Emily; Marshall, Riley A.; Mahalingam, Ramaswami
ABSTRACT: Increasing research has improved global awareness of mistreatment during childbirth. However, research primarily focuses on "higher-intensity" mistreatment during childbirth, and largely focuses on women outside the United States (U.S.). We address these gaps by exploring the phenomenology of incivility, a "lower-intensity" mistreatment, experienced by women during childbirth in the U.S. We used a combination of interpretative phenomenological analysis (IPA) and thematic analysis to analyze the qualitative responses (N = 200) of experiences of incivility during childbirth. We identified nine primary themes of incivility: lack of empathy, denial/minimization, ignoring, pressure, privacy issues, breastfeeding/formula issues, identity-based, uncomfortable physical interactions, and silencing. Results demonstrate incivility is critical to consider as a form of mistreatment in childbirth because it violates respect. The results help nuance the understanding of how mistreatment is experienced in childbirth. Results also demonstrate unique manifestations of incivility were shaped by the sociopolitical context of the U.S. Implications for policy development and health outcomes are discussed.